2015
DOI: 10.1016/j.jvs.2015.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Surgical conversion with graft salvage as a definitive treatment for persistent type II endoleak causing sac enlargement

Abstract: Objective: The goal of this study was to present open surgical conversion with graft salvage or "semiconversion" as a definitive and safe treatment for untreatable and persistent type II endoleaks causing sac enlargement after endovascular aneurysm repair. Methods: Between January 2001 and December 2014, 25 of 1623 endovascular aortic repair (EVAR) patients were selected as candidates for open semiconversion. The indication was persistent type II endoleak in 13 patients (12 of whom received previous attempts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…Moulakakis et al reported that type Ia and Ib endoleaks occurred because of main body and limb dislocations during ligation of the culprit vessels. 19) The recurrence of the endoleak has not been reported, 18,20) but ligating all side branches as much as possible is necessary. Additionally, continuously monitoring new onset endoleaks and infections is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Moulakakis et al reported that type Ia and Ib endoleaks occurred because of main body and limb dislocations during ligation of the culprit vessels. 19) The recurrence of the endoleak has not been reported, 18,20) but ligating all side branches as much as possible is necessary. Additionally, continuously monitoring new onset endoleaks and infections is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The possibility of performing a partial conversion or entirely sparing the endograft has been shown to reduce the risk of the open procedure, 20 but endovascular treatment, when feasible, certainly represents a better option for this high-risk population. [21][22][23] Cuffs are a reasonable approach to treat distal migration with a residual infrarenal neck, but different strategies are necessary when the graft is still in place. Embolization with Onyx and/or coils has been described as an effective option in selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 However, these studies did not exclude other endoleak types nor did they require endovascular coil or Onyx embolization attempts prior to open intervention. Mangialardi et al 36 described 12 patients who underwent open repair for the treatment of pT2EL following failed endovascular interventions; however, banding of the proximal aorta with Teflon (The Chemours Co., Wilmington, DE) for stability was performed prior to sac imbrication around the endograft. More recently, Metrias et al 11 proposed endoaneurysmorrhaphy with stent graft preservation as an effective treatment of pT2EL with sac expansion following EVAR; however, not all patients in this series underwent initial endovascular attempts before proceeding with open conversion.…”
Section: Discussionmentioning
confidence: 99%